2020
DOI: 10.1097/bsd.0000000000001024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Minimal Invasive Versus Biportal Endoscopic Transforaminal Lumbar Interbody Fusion for Single-level Lumbar Disease

Abstract: Study Design: Retrospective study. Objective: The authors aimed to compare the clinical outcomes of biportal endoscopic transforaminal lumbar interbody fusion (BE-TLIF) with those of minimally invasive transforaminal lumbar interbody fusion (MI-TLIF) using a microscope. Summary of Background Data: Lumbar spinal fusion has been widely performed for various lumbar spinal pathologies. Minimally invasive transforaminal interbody fusion using a tubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
123
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 29 publications
6
123
0
1
Order By: Relevance
“…Кроме того, чрескожные эндоскопические технологии апробированы при стабилизации позвоночника [73,74], спондилодисцитах, опухолях, хронической эпидуральной гематоме позвоночника [75][76][77], огнестрельных ранениях [78,79]. В 2020 г. опубликованы первые исследования о применении бипортальной техники чрескожной эндоскопической декомпрессии при грыжах и стенозах позвоночного канала поясничного отдела [80,81]. Этот год также ознаменовался внедрением в клиническую практику электромагнитной навигации при выполнении чрескожных эндоскопических операций на поясничном отделе позвоночника [82].…”
Section: разработка и совершенствование чрескожных видеоэндоскопических операций на поясничном отделе позвоночникаunclassified
“…Кроме того, чрескожные эндоскопические технологии апробированы при стабилизации позвоночника [73,74], спондилодисцитах, опухолях, хронической эпидуральной гематоме позвоночника [75][76][77], огнестрельных ранениях [78,79]. В 2020 г. опубликованы первые исследования о применении бипортальной техники чрескожной эндоскопической декомпрессии при грыжах и стенозах позвоночного канала поясничного отдела [80,81]. Этот год также ознаменовался внедрением в клиническую практику электромагнитной навигации при выполнении чрескожных эндоскопических операций на поясничном отделе позвоночника [82].…”
Section: разработка и совершенствование чрескожных видеоэндоскопических операций на поясничном отделе позвоночникаunclassified
“…Previous studies have reported promising postoperative outcomes [ 91 - 93 ]. Some reports have shown that endoscopic LIF yielded lesser postoperative pain and shorter hospital stay than MIS-TLIF [ 94 ]. Moreover, despite the benefits of endoscopic LIF, there are inevitable obstacles to overcome and surgeons should reach the learning curve [ 92 , 95 - 97 ].…”
Section: Endoscopic Lumbar Interbody Fusionmentioning
confidence: 99%
“…While conventional posterior lumbar interbody fusion (PLIF) or transforaminal lumbar interbody fusion (TLIF) techniques have shown good clinical and radiological outcomes for lumbar degenerative disease, they have also been associated with paraspinal muscle injury from subperiosteal dissections and retraction, which can lead to increased postoperative back pain and muscle atrophy 2,9,18,19) . Threfore, recent techniques for endoscopic lumbar interbody fusion (ELIF) have been developed, which are associated with minimal muscle injury to posterior musculo-ligamentous structures, good clinical outcomes, and satisfactory fusion rates 1,[4][5][6]8,[10][11][12]16,17,[21][22][23] . There are several studies on uniportal ELIF 8,12,17,[21][22][23] , and biportal ELIF has been published by several investigators [4][5][6]10,11,16) .…”
Section: Introductionmentioning
confidence: 99%
“…Unlike uniportal ELIF, independent movement of the endoscope and surgical instruments is possible, and the working portal is used only for surgical instruments not though the working cannula. As a result, biportal ELIF can achieve direct ipsilateral and contralateral decompression similar to MIS TLIF with fewer limitations of motion and vision [4][5][6]10,11,16) . Moreover, biportal ELIF has advantages in terms of minimal invasiveness 5,11,16) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation